Sifat FOMO dalam Gaya Hidup Gen Z: Takut Ketinggalan atau Takut Tidak Dianggap oleh Society? Mengurangi Fenomena FOMO pada Remaja - Mulyaning Wulan; Loudyninta L.A; Putri Atika Wardani; Mutiara Andini; M. Alviansyah; Fajar Ihsan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The rapid development of technology and social media in the digital era has provided many conveniences in daily life, but it has also given rise to the phenomenon of Fear of Missing Out (FOMO) that is widely experienced by Generation Z. FOMO itself is a psychological condition where individuals experience a fear of missing out on information, trends, or activities being undertaken by others. This phenomenon has the potential to affect the mental health, productivity, and decision-making patterns of teenagers. Next, the PKM FEB UHAMKA team is present to accompany and provide training in the form of seminars and interactive Q&A sessions to guide how Generation Z should respond to this FOMO phenomenon.